2021
DOI: 10.1021/acs.energyfuels.1c03189
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Intimate Link between the Surfactant/Oil/Water Phase Behavior and the Successful Design of (Alkali)–Surfactant–Polymer Floods

Abstract: Formulating alkali-surfactant-polymer (ASP) solutions for chemical enhanced oil recovery (EOR) requires detailed phase behavior investigation, especially with some “difficult” crude oils of medium acidity, for which special attention must be paid to the surfactants and alkali selection. In this work, the efficiencies of eight corefloods performed on a real case study in (A)­SP conditions have been related to the phase behavior of the surfactant/crude oil/water (SOW) systems investigated as a function of salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Winsor's R theory on the occurrence of particular phase behavior in surfactant-oil-water (SOW) systems when the interfacial interaction of the adsorbed surfactant with oil and water phases were equal was rediscovered, as has been explained in detail elsewhere [2,84,166]. The point was that the SOW formulation to attain a three-phase behavior in SOW systems corresponded to a (very low) minimum interfacial tension which was crucial for enhanced oil recovery (EOR) with surfactants [127,179].…”
Section: The Normalized Hydrophilic-lipophilic Deviation (Hld N ) As ...mentioning
confidence: 99%
“…Winsor's R theory on the occurrence of particular phase behavior in surfactant-oil-water (SOW) systems when the interfacial interaction of the adsorbed surfactant with oil and water phases were equal was rediscovered, as has been explained in detail elsewhere [2,84,166]. The point was that the SOW formulation to attain a three-phase behavior in SOW systems corresponded to a (very low) minimum interfacial tension which was crucial for enhanced oil recovery (EOR) with surfactants [127,179].…”
Section: The Normalized Hydrophilic-lipophilic Deviation (Hld N ) As ...mentioning
confidence: 99%
“…Nevertheless, elevated salt levels and the presence of multivalent ions often induce the collapse of coherency, and thus, macromolecular solutions (sol) containing individual, separated polymer chains form . Such a sol–gel transition depends not only on the salinity and polymer concentration but also on other factors like temperature, chemical composition, and porosity of the oil reservoir, while it can be tuned by additives including surfactants, , solid particles, or other surface active compounds. , It is obvious from these facts that a direct comparison of the efficiency of EOR polymers can be given only under the same reservoir conditions due to the sensitivity of the sol–gel transition process to environmental factors. , …”
Section: Introductionmentioning
confidence: 99%
“…That is why the salinity of pre-flush fluid is designed to be above optimum salinity. Secondly, various experimental and modeling studies have shown a delay in surfactant breakthrough and reduced surfactant loss as a result of surfactant partitioning into the oleic phase when the pre-flush fluid has a salinity higher than the optimum salinity [58,62,63]. Finally, the postflush or chase fluid of below-optimum salinity can stimulate the partitioning of the retarded surfactant into the aqueous phase, generating Type III through to Type I microemulsion with ultra-low IFT and further reducing surfactant loss [64,65].…”
Section: Introductionmentioning
confidence: 99%